(untitled) (Research, Society and Development, 2021)
Aim: Evaluate the effects of Chiropractic Instrumental Therapy on posture and shape of trunk extensor muscles. Methods: Is a study of the type of quasi-experimental cross-section, with a sample of 31 individuals. A history, then the digital photogrammetry and lumbar hand, both carried out before and after treatment with Instrumental Chiropractic Therapy. For analysis of the variables, the Wilcoxon test was applied. The conclusions were based on a 95% confidence interval and p<0.05. Result: It can be observed that, in relation to the General data, the average age is 22.10 years and the prevalence is of female gender in 71%. As for the English review, there was a statistically significant increase in strength after intervention (p = 0.000). Already in the postural assessment, there was no statistically significant results, however presented a qualitative response suggesting a postural alignment of the volunteers. Conclusion: The use of Chiropractic Instrumental Therapy had beneficial effects in relation to the strength of the trunk extensor muscles, and positively influenced the self-perception of improvement in body posture. Further research on the use of this technique is suggested for further evidence.